Secularization and low fertility: How declining church membership changes couples’ childbearing - Schubert, Henrik-Alexander; Skirbekk, Vegard; Nisén, Jessica (Elsevier, 2026)
Previous studies have shown that secularization altered historical Western fertility patterns, but few studies have addressed the role of religion in the marked fertility declines in recent decades. We examine the relationship between secularization and fertility decline in Finland from a couple perspective, amid a broader trend of declining fertility. We show that secularization can exert a self-reinforcing negative effect on fertility through an interplay of declining church membership and childbearing of religiously mixed and homogeneous couples. Using data from the Finnish administrative registers covering the period from 1995 to 2019, we are able to identify religious affiliation, as measured by church tax payments in the secularized context of Finland. The analysis takes a dyadic perspective to explore the relationships between couples’ religious affiliation and their probability of having a first child. We conclude that the accelerated decline in church membership has contributed to the recent fertility decline.